Production of cellulase from Aspergillus niger and Trichoderma reesei mixed culture in carboxymethylcellulose medium as sole carbon (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Septiani D, Suryadi H, Mun’im A, Mangunwardoyo W. 2019. Production of cellulase from Aspergillus niger and Trichoderma reesei mixed culture in carboxymethylcellulose medium as sole carbon. Biodiversitas 20: 3539-3544. Cellulase is one of hydrolytic enzymes that breakdown cellulose into glucose. Cellulases are promising to be applied in natural products which may improve the yield of bioactive in plant extract through cellulose depolymerization. Cellulases from mixed culture of Aspergillus niger and Trichoderma reesei can produce a high cellulase activity because of the synergism activity among endoglucanase, exoglucanase, and also ?-glucoside. Cellulase production and partial purification of monoculture and mixed culture (1:1) of these fungi on carboxymethylcellulose media were investigated in this study. Total cellulase activity was measured by filter paper assay followed by protein estimation with Bradford method. The crude extract of Aspergillus niger monoculture has the highest cellulase activity (0.131 U/mL, P
Keywords: Aspergillus niger, cellulase, carboxymethyl cellulose, mixed culture, Trichoderma reesei